2021
DOI: 10.3389/fmed.2021.792846
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ketogenic Diet on Inflammatory Arthritis and Cardiovascular Health in Rheumatic Conditions: A Mini Review

Abstract: The principle of ketogenic diet (KD) is restriction of carbohydrates to a maximum of 5–10% of the total daily caloric intake, aiming at shifting body metabolism toward ketone bodies. Different studies suggested promising results of KD to help patients to lose weight, to reduce insulin requirements in diabetes, to supplement cancer protocols, to treat neurological conditions and to optimize control of metabolic and cardiovascular diseases. However, literature about the anti-inflammatory properties of KD in rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 110 publications
0
17
0
1
Order By: Relevance
“…Several studies analysed the link between DISH and diabetes [ 47 , 48 ], and a possible pathogenetic mechanism might be that the high levels of insulin or insulin-like growth factors stimulate new bone formation [ 49 , 50 ]. Indeed, insulin is a bone growth-promoting peptide [ 51 ] and it has been suggested as a key player in the pathophysiology of DISH and of other spinal inflammatory and degenerative disorders, with a potential effect of diet modifications on their management [ 52 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies analysed the link between DISH and diabetes [ 47 , 48 ], and a possible pathogenetic mechanism might be that the high levels of insulin or insulin-like growth factors stimulate new bone formation [ 49 , 50 ]. Indeed, insulin is a bone growth-promoting peptide [ 51 ] and it has been suggested as a key player in the pathophysiology of DISH and of other spinal inflammatory and degenerative disorders, with a potential effect of diet modifications on their management [ 52 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ketogenic diet (KD) involves restricting carbohydrates (to a maximum of 5–10% of total daily caloric intake), which shifts metabolism toward ketone bodies. Research and literature on KD and its anti-inflammatory properties in rheumatic diseases are still limited but have shown promise in helping patients lose weight, reduce insulin requirements in diabetes, and control the metabolic disease that is common in RA patients [ 92 ].…”
Section: Regulation Of Sirt1 As a Potential Target In Ra Therapymentioning
confidence: 99%
“…S4). Although several studies have described the anti-inflammatory properties of a KD (Ciaffi et al, 2021 ; Dupuis et al, 2015 ), others have also observed signs of increased inflammation associated with a KD in mice (Garbow et al, 2011 ) and human subjects (Rosenbaum et al, 2019 ). Thus, no conclusive assumption can be made with regards to a KD and chronic alcohol consumption’s impact on inflammation and further research is required.…”
Section: Metabolic Alterationsmentioning
confidence: 99%